Influence of surfactants on Fe2O3 nanostructure photoanode - Memar, Amir; Phan, Chi; Tade, Moses (Elsevier Ltd, 2012)
Fe2O3 nanostructures photoanodes were prepared via sol-gel spin-coating method onto fluorine-doped tin oxide glass substrates using six different surfactants: polyethylene glycol (PEG-300), Triton X-100, pluronic F127, cetyltrimethylammonium bromide (CTAB), octadecyltrimethylammonium bromide (OTAB) and tetradecyltrimethylammonium bromide (TTAB). The resulting films have thickness from 520 ± 10 to 980 ± 10 nm after calcinations at 450 °C in the air. A comparative study of photocatalytic activity of thin films was performed. The photo-generated samples were determined by measuring the currents and voltages under illumination of UV-vis light. The highest photocurrent density of 1.77 mA/cm2 at 1 V/SCE, under illumination intensity of 100 mW cm-2 from a solarsimulator with a global AM 1.5 filter, were produced by TTAB treated sample. The optical properties, morphology, surface roughness and structure of the films were also characterized by UV-visible spectroscopy, SEM, AFM and XRD. The results are consistent with photocatalytic performance: TTAB treated sample has the highest grain size and optical absorption. The improved performance of this sample can be attributed to the crystallinity process of TTAB, which leads to the larger grain size and highest photocatalytic activity. The study demonstrates that photoelectrochemical performance of metal oxide can be improved by simply changing surfactant. The results highlighted the superior performance of cationic surfactants over non-ionic surfactants in preparing Fe2O3 photoanodes by sol-gel method. Moreover, the study showed that decreasing hydrocarbon tail of cationic surfactants can increase the crystallite size and improve photocatalytic activity.